Effect of the Tube Bundle Configuration on the Experimental Two-Section Two-Zone Fluidized Bed Reactor Hydrodynamics - Julián, Ignacio; Gallucci, Fausto; van Sint Annaland, Martin; Herguido, Javier; Menéndez, Miguel (Jornada de Jóvenes Investigadores del I3A, 2017)
Particle Image Velocimetry (PIV) and Digital Image Analysis (DIA) techniques have been used to study the effect of different tube bundle configurations on the hydrodynamic behaviour of a novel gas-solid catalytic reactor concept, the so called: Two-Section Two-Zone Fluidized Bed Reactor.